Rotor Speed Estimation Method Used in Dynamic Control of the Induction Motor - CRĂCIUNAŞ Gabriela (Journal of Electrical and Electronics Engineering, 2013)
In this paper it is proposed an algorithm for rotor speed estimation calculated directly from the rotor flux. The flux required for speed computation is estimated using Gopinath reduced order robust adaptive observer. In order to determine the structure of the observer we started from the state equations of the induction motor using spatial vectors written in fixed coordinates towards stator and considering the rotor speed constant. Quality of speed and rotor fluxestimation was evaluated from the results obtained during different operation regimes. The proposed algorithm was then tested for its usability in the case of indirect field oriented control based on the rotor flux of the induction motor by the simulation inMATLAB/Simulink.